2021
DOI: 10.1038/s41420-021-00641-7
|View full text |Cite
|
Sign up to set email alerts
|

Axonal degeneration induces distinct patterns of phosphatidylserine and phosphatidylethanolamine externalization

Abstract: Axonal degeneration is a common feature of multiple neurodegenerative diseases, yet the mechanisms underlying its various manifestations are incompletely understood. We previously demonstrated that axonal degeneration is associated with externalization of phosphatidylserine (PS), which precedes morphological evidence of degeneration, is redox-sensitive, and is delayed in Wallerian degeneration slow (WldS) mutant animals. Phosphatidylethanolamine (PE) is the other major membrane phospholipid in the inner leafle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
(52 reference statements)
0
2
0
Order By: Relevance
“… 20 , 21 It is also possible that the spread of axonal injury is related to PS externalization, which is an “eat-me” signal for macrophages or other phagocytic cells. 22 , 23 An activation of phagocytosis of primarily injured axons could result in a bystander effect for adjacent axons within the same axonal bundle.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 It is also possible that the spread of axonal injury is related to PS externalization, which is an “eat-me” signal for macrophages or other phagocytic cells. 22 , 23 An activation of phagocytosis of primarily injured axons could result in a bystander effect for adjacent axons within the same axonal bundle.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that phosphatidylserine is a lipid in cells exposed to the surface after axonal injury (Faris et al, 2021). Phosphatidylserine is essential in identifying and promoting axon fusion and regeneration after injury…”
Section: Engineering Exosomes Modified With Aptamersmentioning
confidence: 99%
“…The phospholipid phosphatidylserine (PS), which is normally present primarily in the inner leaflet of the plasma membrane and excluded from the outer leaflet of healthy neurons 50 , is exposed on the external leaflet of the axon membrane during bioenergetic stress 21 . Moreover, exposed PS is concentrated on axonal swellings 22,51 . Up until this point, nearly all studies on PS exposure on compromised axons have been done in acute injury conditions [21][22][23]51 .…”
Section: Sarm1 Activation Triggers Membrane Ps Exposure On Stressed-b...mentioning
confidence: 99%
“…Moreover, exposed PS is concentrated on axonal swellings 22,51 . Up until this point, nearly all studies on PS exposure on compromised axons have been done in acute injury conditions [21][22][23]51 . Here we leveraged our dKO model to examine whether PS exposure also occurs with chronic SARM1 activation.…”
Section: Sarm1 Activation Triggers Membrane Ps Exposure On Stressed-b...mentioning
confidence: 99%